2019
DOI: 10.1017/s0022377819000321
|View full text |Cite
|
Sign up to set email alerts
|

Collisional alpha transport in a weakly non-quasisymmetric stellarator magnetic field

Abstract: Alpha particle confinement is a serious concern in stellarators and provides strong motivation for optimizing magnetic field configurations. In addition to the collisionless confinement of trapped alphas in stellarators, excessive collisional transport of the trapped alpha particles must be avoided while they tangentially drift due to the magnetic gradient (the $\unicode[STIX]{x1D735}B$ drift). The combination of pitch angle scatter off the background ions and the $\un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…in agreement with the tokamak limit of scaling evaluated by Catto (2019b). However, for finite magnetic shear s = rq −1 ∂q/∂r ∼ 1, have shown that the sign reversal of the drift occurs very close to the trapped-passing boundary so that the resonant plateau and √ ν (Calvo et al 2017) transport regimes merge and this estimate becomes sensitive to shear.…”
Section: Ripple Transport Of Alphassupporting
confidence: 83%
See 1 more Smart Citation
“…in agreement with the tokamak limit of scaling evaluated by Catto (2019b). However, for finite magnetic shear s = rq −1 ∂q/∂r ∼ 1, have shown that the sign reversal of the drift occurs very close to the trapped-passing boundary so that the resonant plateau and √ ν (Calvo et al 2017) transport regimes merge and this estimate becomes sensitive to shear.…”
Section: Ripple Transport Of Alphassupporting
confidence: 83%
“…Very similar arguments to those in the preceding section are next used to make estimates for ripple transport in the superbanana plateau regime (Galeev et al 1969;Shaing 2015;Catto 2019b). They allow a bound on the ripple amplitude to be estimated.…”
Section: Ripple Transport Of Alphasmentioning
confidence: 99%
“…This role is directly analogous to that played by collisionality in superbanana plateau tokamak transport (see discussion in Shaing (2015), Calvo et al. (2017) and Catto (2019 a )). It is also similar to the role played by collisionality in the plateau regime of neoclassical transport (see Helander & Sigmar 2005), in the damping of plasma echoes (see Su & Oberman 1968) and in other wave–particle resonance processes (Duarte et al.…”
Section: Plasma Response To Perturbationsmentioning
confidence: 71%
“…At low collisionalities, estimates indicate that the transitional ions widen the trapped-passing boundary layer to introduce a regime linear in ν * (Beidler et al 2011;Catto 2019) that cannot be treated by the procedures herein.…”
Section: A Spurious Non-omnigenous Collisional Tangential Drift Modifmentioning
confidence: 97%